FIELD APPLICATION OF ABOLIC STEROIDS IN CARP SEED PRODUCTION I REARING OF FRY TO FINGERLING STAGE - VENKAILSHVARAN, K.; VENUGOPAL, G.; REDDY, R.R.K. (Journal of Indian Fisheries Association, 2015)
Ethylestrenol (17 Hydroxy-17 as ..ethyl-estr-4-en-3-one) and Stanozolal (17(3 - Hydroxy17 a -methy 1-5 a -androstano - (3,2-C)- pyrazole), both synthetic androgenic steroids, werefed via diet at 3 ppm to the fry of catla,rohu and silver carp which were reared upto fingerlingstage over a period of 167-172 days in earthen ponds. Ethylestrenol enhanced growth in silvercarp and rohu but retarded growth in catla. Stanozolal depressed growth in all the 3 species.Length-weight relationship for these fry had been worked out and the relative condition factorin all the cases was very close to or slightly above 1.0.